Improving the Performance of Paper Supercapacitors Using Redox Molecules from Plants. (24th June 2019) - Edberg, Jesper; Brooke, Robert; Granberg, Hjalmar; Engquist, Isak; Berggren, Magnus
Abstract: A supercapacitor made from organic and nature‐based materials, such as conductive polymers (PEDOT:PSS), nanocellulose, and an the organic dye molecule ( alizarin ), is demonstrated. The dye molecule, which historically was extracted from the roots of the plant rubia tinctorum, is here responsible for the improvement in energy storage capacity, while the conductive polymer provides bulk charge transport within the composite electrode. The forest‐based nanocellulose component provides a mechanically strong and nonporous network onto which the conductive polymer self‐organizes. The electrical and electrochemical properties of the material composition are investigated and prototype redox‐enhanced supercapacitor devices with excellent specific capacitance exceeding 400 F g −1 and an operational stability over >1000 cycles are demonstrated. This new class of supercapacitors, which in part are based on organic materials from plants, represents an important step toward a green and sustainable energy technology. Abstract : The redox‐active dye molecule alizarin is used to enhance the energy storage capacity of all‐organic paper‐supercapacitors. The electrochemical performance and secondary doping effect of the dye on the conductive polymer PEDOT:PSS is investigated, and symmetric redox‐enhanced supercapacitor devices are demonstrated. This research shows how materials from plants can be used for green energy storage technologies.